2020
DOI: 10.26717/bjstr.2020.31.005048
|View full text |Cite
|
Sign up to set email alerts
|

Subtypes of Subcutaneous Angioleiomyoma on High- Resolution Color Doppler Ultrasonography along with MRI Appearances

Abstract: ALM is a rare tumor that arises from the tunica media of small arteries and veins [1]. ALM typically occurs in the cutaneous, subcutaneous tissue of the lower extremities in middle-aged women. Histological appearances show a proliferation of smooth muscle cells and vascular channels and the classification into three histological subtypes such as solid (or capillary), cavernous, and venous types has been defined [1]. The author has previously described the solid (or capillary) subtype of ALM as a painful and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 36 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…The author has previously described the solid (or capillary) subtype of ALM as a painful and vascularized subcutaneous tumor, probably in close to the dermis [2] and indicated that all painful cutaneous and subcutaneous tumors including ALM used as the acronym "ENGLAND" or "LEND an EGG" [3], especially, angioleiomyoma, eccrine spiradenoma, schwannoma, and glomus tumor show vascularlized appearances on high-resolution color Doppler US [4]. The author also described the subtypes of subcutaneous angioleiomyoma on high-resolution color Doppler ultrasonography along with MRI appearances [5]. In solid subtype, little vascularity and adjacent vessel features on color and power Doppler US and enhancing structures on one or both ends of the mass on magnetic resonance imaging may be a potential diagnostic findings as previously described [5].…”
Section: Us and Mri Aappearances In Angioleiomyomamentioning
confidence: 99%
See 2 more Smart Citations
“…The author has previously described the solid (or capillary) subtype of ALM as a painful and vascularized subcutaneous tumor, probably in close to the dermis [2] and indicated that all painful cutaneous and subcutaneous tumors including ALM used as the acronym "ENGLAND" or "LEND an EGG" [3], especially, angioleiomyoma, eccrine spiradenoma, schwannoma, and glomus tumor show vascularlized appearances on high-resolution color Doppler US [4]. The author also described the subtypes of subcutaneous angioleiomyoma on high-resolution color Doppler ultrasonography along with MRI appearances [5]. In solid subtype, little vascularity and adjacent vessel features on color and power Doppler US and enhancing structures on one or both ends of the mass on magnetic resonance imaging may be a potential diagnostic findings as previously described [5].…”
Section: Us and Mri Aappearances In Angioleiomyomamentioning
confidence: 99%
“…Recently, the study using the ultra-highfrequency ultrasound in the evaluation of pediatric pilomatricoma has been reported [11]. The author usually performs US studies for dermatologic fields with a high-resolution, broad-band (5MHz-18MHz) linear transducer (Nobulus Hitachi, Ltd.Tokyo, Japan) and described several reports in the dermatologic area [2,4,5,[12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Ultrasound In Dermatologymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Yang et al [2] described that the target sign is a prominent feature on US in peripheral schwannoma. The author usually performs US studies for dermatologic fields with a high-resolution, broad-band (5MHz-18MHz) linear transducer (Nobulus Hitachi, Ltd. Tokyo, Japan) and described several studies including schwannoma [4][5][6][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Ultrasound In Dermatologymentioning
confidence: 99%
“…The author has also mentioned that it is important to differentiate between schwannoma and angioleiomyoma (ALM) [5,6]. It has been suggested that nerve-tumor associations such as nerve-tumor position and neve-tumor transition are significant features to differentiate schwannoma from neuroma [7,8].…”
Section: Introductionmentioning
confidence: 99%